PEDAGOGICAL EDUCATION OF TIMOTHY LUBENTSOV (END XIX - THE FIRST THIRD OF THE TWENTIETH CENTURY) - Venhlovska, Оlena А. (Educological discourse, 2015)
In this paper, the results of the study of theoretical sources, materials from the collections of the Pedagogical Museum of Ukraine (Case T Lubenets) discloses the direction and content of teacher education of outstanding teacher, educator, ascetic late XIX - the first third of the twentieth century, Timothy G. Lubenets. It was found that in certain chronological framework of the research T. Lubenets exerted a lot of effort for the development of public preschool education, teacher education, adult education, the spread of education and literacy. On the initiative and with the assistance of a teacher in Kiev and the Kiev province opened libraries, public schools, evening classes for adults, folk kindergartens, created educational centers.